2005
DOI: 10.1002/app.22371
|View full text |Cite
|
Sign up to set email alerts
|

Response of a sequential‐valve‐gate system used for thin‐wall injection molding

Abstract: Sequential injection molding using a valvegate-controlled hot runner system has attracted attention for industrial applications in recent years. Because of the complexity of the operation mechanisms, a commercial valve gate usually delays for about 0.3-0.5 s once the valve-opening command is given. The signal-to-operation delay is acceptable for the conventional injection molding of large parts. However, this operation delay limits its application to thin-wall molded parts for computer, communication, and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…The delay in the sequential valve gate system is critical to control the filling time during plastic injection molding. Chen et al [13] found that the commercially sequential valve gate system delay time is from 0.3 to 0.5 seconds and most affected by the pneumatic control system air pressure responding to the valve opening and closing. Larger air pressure of 100 bars may give a shorter delay time of fewer than 15 milliseconds, and this more accurate control of the on/off switch valve helps connect the flow fronts to reduce the filling pressure loss.…”
Section: Introductionmentioning
confidence: 99%
“…The delay in the sequential valve gate system is critical to control the filling time during plastic injection molding. Chen et al [13] found that the commercially sequential valve gate system delay time is from 0.3 to 0.5 seconds and most affected by the pneumatic control system air pressure responding to the valve opening and closing. Larger air pressure of 100 bars may give a shorter delay time of fewer than 15 milliseconds, and this more accurate control of the on/off switch valve helps connect the flow fronts to reduce the filling pressure loss.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous remedies have been developed to eliminate the problem of a weak weld-line structure. These include control processing parameters [4 -7] to enhance the strength in the weldline area, changing geometry and gate locations [8,9] , applying additional schemes to increase the melt temperature [10,11] , and developing theoretical models to predict weld-line strength [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Their experimental results indicated that the overflow trap can change the location of weld lines and move these defects into an unimportant area. Chen et al8 developed a gas‐driven sequential valve gate system for molding parts with thin walls. The system supported the rapid control of the sequence in which the gates are used to allow the melt to fill the cavity.…”
Section: Introductionmentioning
confidence: 99%